Analisis Determinan Tingkat Pengangguran Kabupaten/Kota Di Jawa Tengah Tahun 2010-2015 - Nurjanah, Miftah Intan; , Dr. Didit Purnomo, S.E.,M.Si (2017)
This study aims to mngetahui unemployment rate in the district / city in Central Java 2010-2015. And how big factors that affect the level of unemployment in Central Java in 2010-2015 was influential. The analytical tool used is multiple linear regression on the data panel, by retrieving data using secondary data derived from the library, books, websites, journals or reports of similar studies and of the agency or institution related such as the Badan Pusat Statistik (BPS), Badan Perencana Pembangunan Daerah (Bappeda) These results indicate that the minimum wage of employees partially affect the unemployment rate in the district / city in Central Java, while inflation, poverty, and the GDP is not partial effect. The minimum wage employees, inflation, poverty, and the GDP together greatly affect the unemployment rate in the district / city in Central Java. Minmum wage employees, inflation, poverty levels are able to explain the unemployment rate in the district / city in Central Java at 14.9673%. Thus the government should pay attention to minimum wage employees to the unemployment rate decreases. Keywords: Employee Minimum Wages, Inflation, poverty rate, the GDP, Unemployment Rate